Kepemimpinan SDM dalam Era Quantum Workforce: Menyiapkan Talenta untuk Industri Komputasi Masa Depan (Fokus: Strategi Pengembangan Kompetensi yang Melampaui Literasi Digital Standar) - Dyah Ayu Pramudita; Revi Agustina; Saifatul Dwi Fitrianti; Mochammad Isa Ansori (Jurnal Mahasiswa Manajemen dan Akuntansi, 2026)
The emergence of quantum computing is driving a fundamental shift in workforce competency requirements, challenging the adequacy of conventional digital literacy frameworks. This study aims to identify key competencies in the quantum workforce era, evaluate the limitations of traditional digital literacy, and analyze the strategic role of human resource leadership in future-oriented talent development. This research employs a systematic literature review (SLR) of reputable academic publications from the past five years. The findings reveal that required competencies are inherently multidimensional, encompassing advanced technical expertise, higher-order cognitive skills, interdisciplinary capabilities, and adaptive capacity grounded in lifelong learning. Conventional digital literacy is insufficient to address the probabilistic and non-linear nature of quantum computing systems. Human resource leadership plays a strategic role in driving competency transformation through innovation, orchestration of continuous learning, and alignment of talent strategies with technological dynamics. This study contributes to the advancement of competency development frameworks beyond traditional approaches and offers practical implications for organizations in building a resilient and future-ready workforce